Attitudes of parents towards paediatric palliative care : a medical social work intervention perspective in the Limpopo Province, South Africa - Mogale, Rudzani Noria (My University, 2023)
Case study design was used to explore parents’ attitudes towards paediatric palliative care in Limpopo Province, South Africa. Semi-structured in-depth face-to-face interviews were used as a main method of collecting data. Purposive sampling was used to select twenty (20) participants to be involved in the study which were ten (10) parents and ten (10) caregivers of children with cancer who were admitted in the Paediatric Oncology ward within the Polokwane hospital in the Limpopo Province. A Content analysis was used to analyse the data which encompassed ATLAS.ti software. The results showed that parents and caregivers of children suffering from cancer and admitted in Paediatric Palliarive ward at Polokwane hospital, had a generally positive attitude towards PPC. The participants’ perspectives on their own emotional, social, financial, and psychological health because of caring for a child with cancer are mixed, with most parents reporting that they are striving to cope with the situation. In relation to challenges that temper with their coping, other participants made mention of their financial battle and losses incurred in their search for a cure for their child's illness. The study also revealed positive support received from health workers and family members. Regarding the knowledge of PPC, results indicate that parents do not have sufficient information regarding the meaning of PPC. The results also revealed lack ofreferrals by social workers for PPC and lack of cooperation between health workers and social workers. The researcher concluded that the support provided to parents improves their knowledge and awareness of PPC services, and consequently, changes their ‘negative’ attitudes towards PPC. Thus, they begin to trust the system being certain that their children will receive better treatment in PPC.
Thesis (M.A. (Social Work)) -- University of Limpopo, 2023
Keywords: Paediatric palliative; Parents’ attitudes; Caregivers; Cancer; Social work; Palliative treatment -- Periodicals -- South Africa -- Limpopo Province; Critical Care -- Methods -- South Africa -- Limpopo Province; Cancer in adolescence -- Palliative treatment -- South Africa -- Limpopo Province; Pediatrics; Cancer -- Patients -- Hospital care